Mixtecan learning landscape, datascape - Lopez-Ridaura, Santiago; Zepeda, Adair; Orozco-Ramirez, Quetzalcoatl; Reyna Ramirez, Cristian Alejandro; Fuentes Ponce, Mariela (CIMMYT, 2025)
The Datascape component of the Mixtecan Learning Landscape is a digital solution to gather publica available information to support research activities for different actors interested in the region (students, scientists, researchers, authorities, policy makers). In that place a wide range of information is offered under published documents or raw anonymized datasets for research purposes.